Indomethacin Increases the Efficacy of Oxygen Utilization of Colonic Mitochondria and Uncouples Hepatic Mitochondria in Tissue Homogenates From Healthy Rats - Herminghaus, Anna; Buitenhuis, Albert J.; Schulz, Jan; Truse, Richard; Vollmer, Christian; Relja, Borna; Bauer, Inge; Picker, Olaf (Frontiers in Medicine, 2020)
Background: Studies suggest that indomethacin (Indo) exhibits detrimental changes in the small intestine (microvascular disorder, villus shortening, and epithelial disruption), mainly due to mitochondrial uncoupling. The effects of Indo on colon and liver tissue are unclear. The aim of this study was to determine the effects of Indo on mitochondrial respiration in colonic and hepatic tissue. Methods: Mitochondrial oxygen consumption was assessed in colon and liver homogenates from healthy rats. Homogenates were incubated without drug (control) or Indo (colon: 0.36, 1, 30, 179, 300, 1,000, 3,000 μM; liver: 0.36, 1, 3, 10, 30, 100, 179 μM; n = 6). State 2 (substrate-dependent) and state 3 (ADP-dependent respiration) were evaluated with respirometry. The respiratory control index (RCI) was derived and the ADP/O ratio was calculated. Statistics: Data presented as % of control, min/median/max, Kruskal–Wallis+Dunn's correction, *p < 0.05 vs. control. Results: Indo had no effect on RCI of colonic mitochondria. ADP/O ratio increased in complex I at concentrations of 1,000 and 3,000 μM (Indo 1,000 μM: 113.9/158.9/166.9%*; Indo 3,000 μM: 151.5/183.0/361.5%*) and in complex II at concentrations of 179 and 3,000 μM vs. control (179 μM: 111.3/73.1/74.9%*; 3,000 μM: 132.4/175.0/339.4%*). In hepatic mitochondria RCI decreased at 179 μM for both complexes vs. control (complex I: 25.6/40.7/62.9%*, complex II: 57.0/73.1/74.9%*). The ADP/O ratio was only altered in complex I at a concentration of 179 μM Indo vs. control (Indo 179 μM: 589.9/993.7/1195.0 %*). Conclusion: Indo affected parameters of mitochondrial function in an organ-specific and concentration-dependent manner. In colonic tissue, RCI remained unaltered whereas the ADP/O ratio increased. Indo at the highest concentration decreased the RCI for both complexes in hepatic mitochondria. The large increase in ADP/O ratio in complex I at the highest concentration likely reflects terminal uncoupling.